English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I would like the procedure, not only the result.

2006-12-12 12:02:24 · 3 answers · asked by Strabos 2 in Science & Mathematics Mathematics

3 answers

ax = a-3x if and only if
ax + 3x = a if and only if
(a+3)x=a if and only if
x = a/(a+3)

so assuming you know what a is, and a doesn't equal -3, the solution is x = a/(a+3)

2006-12-12 12:05:57 · answer #1 · answered by socialistmath 2 · 0 0

ax = a - 3x
Add 3x to both sides to get all the x on the same side
Factor x from the common terms on the left side
Divide both sides by the result
Don't look any further down if you don't want the answer
.
.
.
.
.
.
ax + 3x = a
(a+3)x = a
x = a/(a+3)

2006-12-12 12:08:18 · answer #2 · answered by Steve A 7 · 0 0

ax=a-3x
ax+3x=a
x(a+3)=a
x=a/(a+3)

2006-12-12 12:06:12 · answer #3 · answered by Anonymous · 0 0

fedest.com, questions and answers